OPTIMALISASI HASIL BELAJAR SISWA KELAS IV DALAM PEMBELAJARAN IPS DENGAN MEDIA AUDIOVISUAL DI SEKOLAH DASAR - Lulie Hana Fairuzy; Asiyah Amira Refah; Rivanda Isnichaeni Chandra; Syifa Azzahra Erina Putri; Wati Sukmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the importance of learning in achieving national education goals and the role of teachers in implementing effective learning methods. The research problem identified was the low learning achievement of students in social studies subjects at SDN East Jakarta, especially in class IV. The aim of this research is to improve student learning outcomes in social studies subjects through the use of audiovisual media. The research methodology used is the Quantitative Descriptive method, with data collection through observation and interviews. The research results show that the use of audiovisual media has increased students' interest in learning, but some students still experience difficulties in understanding concepts. Through two cycles of classroom action research, improvements were made to learning methods, such as involving students more actively in the learning process and using clearer audiovisual teaching aids. Research findings show that student engagement and learning effectiveness increased over the course of the study. Research implications show that including audiovisual media in social studies teaching can increase students' motivation and understanding of the subject. This research highlights the importance of interactive and engaging teaching methods in improving student learning outcomes.